Nephrocalcinosis fortuitously discovered: the role of surreptitious self administration of diuretics - Nery Sablon Gonzalez; Liliana Moran Caicedo; Maria Belen Alonso Ortiz; Yanet Parodis Lopez; Angelica Laurin; Emmanuel Andrès; Noel Lorenzo Villalba (Babol University of Medical Sciences, 2024)
Background: Furosemide is a drug widely used for several medical conditions and could be used without medical prescription. Furosemide-related nephrocalcinosis can occur regardless of age, although the risk is higher in premature infants. The defining characteristic of nephrocalcinosis is generalized calcium deposition in the kidney. The most useful imaging studies for evaluation are ultrasonography and computed tomography (more effective in detecting calcification). Case Presentation: A 32-year-old woman with a history of depressive syndrome was admitted for evaluation of fortuitously discovered nephrocalcinosis and hypokalemia. The studies performed revealed the presence of a metabolic alkalosis with discrete hyperreninism/hyperaldosteronism but normal ratio, normotension and urinary study showed elevated sodium, chloride, potassium and calcium fluctuating in different determinations. Surreptitious diuretic intake was suspected and urine analysis revealed doses equivalent to 80-120 mg. The patient was advised to discontinue all diuretic treatment; she was adequately supplemented with potassium and she was followed-up in outpatient clinics. During the follow-up, clinical and analytical improvement was noted, which led to the discontinuation of supplementation. Conclusion: Surreptitious diuretic intake is a clinical condition to rule out in patients with chronic hypokalemia, metabolic alkalosis with elevated urinary sodium and chloride. The relation between surreptitious diuretic intake and nephrocalcinosis has not been fully elucidated in adults.